2019
DOI: 10.1155/2019/4528616
|View full text |Cite
|
Sign up to set email alerts
|

ROS Induced by KillerRed Targeting Mitochondria (mtKR) Enhances Apoptosis Caused by Radiation via Cyt c/Caspase-3 Pathway

Abstract: During radiotherapy, reactive oxygen species- (ROS-) induced apoptosis is one of the main mechanism of radiation. Based on KillerRed which can induce ROS burst in different cell substructures, here we hypothesized that KillerRed targeting mitochondria (mtKR) could induce ROS to enhance apoptosis by radiation. In this study, empty vector, mtKR, and mtmCherry plasmids were successfully constructed, and mitochondrial localization were detected in COS-7 and HeLa cells. After HeLa cells were transfected and irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Moreover, the mechanisms involved in photoactivated NBC cell death leading to free radical apoptosis of CSCs remain unknown, as cell death may be caused by distinct, but overlapping, signaling pathways that respond to different stimuli [78]. Cell death pathways and signaling mechanisms can be studied by numerous metabolic studies, including RT-PCR caspase signaling identification, Cytochrome C and ROS identification and DNA destruction [79]. The aforementioned recommendations will aim to address any limitations observed in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mechanisms involved in photoactivated NBC cell death leading to free radical apoptosis of CSCs remain unknown, as cell death may be caused by distinct, but overlapping, signaling pathways that respond to different stimuli [78]. Cell death pathways and signaling mechanisms can be studied by numerous metabolic studies, including RT-PCR caspase signaling identification, Cytochrome C and ROS identification and DNA destruction [79]. The aforementioned recommendations will aim to address any limitations observed in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is an anti-apoptotic protein, which belongs to the Bcl-2 family of proteins, and is considered a classical biomarker of the mitochondrial pathway of apoptosis (27). In apoptosis, external stimuli, such as cytotoxic agents, could result in mitochondrial dysfunction, and then result in the release of pro-apoptotic protein Cyt c and activation of caspases to induce apoptosis (28). Previous studies demonstrated that the dissociation of the Bcl-2/Bax complex can lead to the release of Cyto C (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The genes and their PPI networks highlight their involvement in cell cycle arrest upon detection of DNA damage, affecting DNA replication and repair. During course of DDR, ROS from radiation seems to promote mitochondrial-induced apoptosis [61]. Further, a constant but varying amount of inflammatory responses due to tissue injury (normal and tumor) appears to trigger ROS-induced mitochondrial oxidation [62], which exacerbates local inflammation in nearby tissues and propagates this DNA repair-inflammation stress cycle.…”
Section: Discussionmentioning
confidence: 99%